Prevention of Pruritis following Spinal Morphine for Scheduled Cesarean Birth. Issue 2 (March 2021) - Payne, Christopher; Curtis, Brian; Dan, Devon; Dunston, Shaun; Moore, Chad; Hefley, Justin
Abstract: Background: Intrathecal morphine provides effective analgesia after cesarean birth, yet up to 90% of women who receive it experience excessive itching, an undesirable dose-dependent effect. Pruritis may increase nursing workload, delay breastfeeding, and decrease patient satisfaction. When 0.1 mg spinal morphine is given, pruritis is markedly reduced while analgesia is preserved. Purpose: The purpose of this project was to determine possible causes and solutions for pruritus after cesarean birth. Methods: Anesthesia providers were educated and encouraged to limit spinal morphine to 0.1 mg as a strategy to prevent pruritus. In a repeated measures design, the rate of treatment-required pruritus and opioid consumption were measured 24 hours after surgery. The project included an evaluation of 30 medical records before and 30 medical records after the project intervention. Results: Preintervention rate of treatment-required pruritis was 37%, all received spinal morphine ≥ 1.5 mg. Postintervention rate of treatment-required pruritis was 13% and 57% after spinal morphine 0.1 mg and 0.2 mg, respectively. Opioid consumption was similar between groups. Clinical Implications: Mother–baby nurses can have an impact on the practice of anesthesia providers by advocating for evidence-based dosing of intrathecal morphine to reduce the incidence of pruritis while maintaining effective analgesia for women after cesarean birth. Abstract : Pruritis after cesarean birth with spinal anesthesia using morphine is dose-related and common among women postpartum. In this quality improvement project, the anesthesia team encouraged their providers to use a standardized and lower than routine dose of morphine to decrease risk of pruritis. Most anesthesia providers used the lower dose and fewer women experienced pruritis after scheduled cesarean birth when comparing rates before and after the project was initiated.